Lateral Fast Muscle Fibers Originate From the Posterior Lip of the Teleost Dermomyotome - Steinbacher, P. (2008)
The predominant source of myogenic cells in vertebrates is the dermomyotome (DM). In teleost fish, recent research has provided a useful but limited picture of how myogenic precursors originate from the DM and how they develop into muscle fibers. Here, we combine detailed morphological analysis with examination of molecular markers in trout to describe the cellular mechanisms by which the lateral fast muscle growth zone is created during second phase myogenesis. Results suggest that this occurs by lateral-to-medial immigration of myogenic cells de-epithelializing from the posterior DM lip. These cells then appear to stop proliferation and migrate anteriorly to finally differentiate into muscle fibres. This seems to be a continuation of the rotational cell movement that creates the teleost DM during early somite development. These findings suggest an evolutionary conserved role of the posterior DM lip in amniotes and fish.